Down to Earth With Nuclear Electromagnetic Pulse: Realistic Surface Impedance Affects Mapping of the E3 Geoelectric Hazard. Issue 8 (18th August 2021) - Love, Jeffrey J.; Lucas, Greg M.; Murphy, Benjamin S.; Bedrosian, Paul A.; Rigler, E. Joshua; Kelbert, Anna
Abstract: An analysis is made of Earth‐surface geoelectric fields and voltages on electricity transmission power‐grids induced by a late‐phase E3 nuclear electromagnetic pulse (EMP). A hypothetical scenario is considered of an explosion of several hundred kilotons set several hundred kilometers above the eastern‐midcontinental United States. Ground‐level E3 geoelectric fields are estimated by convolving a standard parameterization of E3 geomagnetic field variation with magnetotelluric Earth‐surface impedance tensors derived from wideband measurements acquired across the study region during a recent survey. These impedance tensors are a function of subsurface three‐dimensional electrical conductivity structure. Results, presented as a movie‐map, demonstrate that localized differences in surface impedance strongly distort the amplitude, polarization, and variational phase of induced E3 geoelectric fields. Locations with a high degree of E3 geoelectric polarization tend to have high geoelectric amplitude. Uniform half‐space models and one‐dimensional, depth‐dependent models of Earth‐surface impedance, such as those widely used in government and industry reports informing power‐grid vulnerability assessment projects, do not provide accurate estimates of the E3 geoelectric hazard in complex geological settings. In particular, for the Eastern‐Midcontinent, half‐space models can lead to (order‐one) overestimates/underestimates of EMP‐induced geovoltages on parts of the power grid by as much as ± 1, 000 volts (a range of 2, 000 volts)—comparable to the amplitudes of the geovoltages themselves. Plain Language Summary: A nuclear explosion in the near‐Earth space environment can produce an electromagnetic pulse (EMP) at the Earth's surface. A low‐frequency part of the EMP signal, known as E3 and covering periods from about a tenth of a second to a few hundred seconds, can induce geoelectric fields in the conducting solid Earth, interfering with the operation of electricity power grids. To investigate this, accurate estimates are required of the Earth's surface impedance—that is, the relationship between geomagnetic and geoelectric field variation. Surface impedance is a function of the electrical conductivity of subsurface rock structures. Using impedance tensors obtained from survey measurements, time‐dependent scenario maps are constructed of the E3 geoelectric fields and power‐grid geovoltages that would be generated by a hypothetical nuclear explosion above the United States. Over the course of the scenario, geoelectric amplitude, polarization, and variational phase are shown to differ significantly from one location to another, mostly as the result of geographic granularity in impedance. It is concluded that extremely simple impedance models, such as those widely used in government and industry reports concerned with power‐grid vulnerability assessment, do not generally provide accurate estimates of the E3 geoelectric hazard in complex geological settings. Key Points: Local differences in surface impedance distort the amplitude, polarization, and variational phase of induced E3 electromagnetic pulse (EMP) geoelectric fields Half‐space models of Earth‐surface impedance do not generally provide accurate estimates of the E3 geoelectric hazard in complex geological settings Until a realistic treatment is made of Earth‐surface impedance, the E3 EMP hazard is not being accurately mapped